2007
DOI: 10.3748/wjg.v13.i3.349
|View full text |Cite
|
Sign up to set email alerts
|

Red wine and green tea reduce H pylori- or VacA-induced gastritis in a mouse model

Abstract: AIM:To investigate whether red wine and green tea could exert anti-H pylori or anti-VacA activity in vivo in a mouse model of experimental infection. METHODS:Ethanol-free red wine and green tea concentrates were administered orally as a mixture of the two beverages to H pylori infected mice, or separately to VacA-treated mice. Gastric colonization and gastric inflammation were quantified by microbiological, histopathological, and immunohistochemical analyses. RESULTS:In H pylori -infected mice, the red wine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 32 publications
2
36
0
Order By: Relevance
“…Oral administration of green tea catechins in combination with sucralfate in Mongolian gerbils infected with H. pylori revealed that the colony-forming units (CFU) of H. pylori was significantly decreased (Takabayashi et al, 2004). In line with these findings, another study revealed that green tea concentrates could influence gastric colonization or gastric pathology in H. pylori-infected or VacA-treated mice (Ruggiero et al, 2007). , 2008).…”
Section: Camellia Sinensismentioning
confidence: 86%
“…Oral administration of green tea catechins in combination with sucralfate in Mongolian gerbils infected with H. pylori revealed that the colony-forming units (CFU) of H. pylori was significantly decreased (Takabayashi et al, 2004). In line with these findings, another study revealed that green tea concentrates could influence gastric colonization or gastric pathology in H. pylori-infected or VacA-treated mice (Ruggiero et al, 2007). , 2008).…”
Section: Camellia Sinensismentioning
confidence: 86%
“…Wine constituents have exhibited antibiotic activity against H. pylori isolates and protected against associated gastric damage in mice (Daroch et al 2001, Mahady et al 2003, Ruggiero et al 2007, Martini et al 2009.…”
Section: Gastrointestinal Effectsmentioning
confidence: 99%
“…The polyphenol compounds may form aggregates with the toxin, in turn preventing its receptor binding and internalization into the host cell (27). A recent finding by Ruggiero et al (19) found that red wine was able to prevent H. pylori-induced gastric epithelium damage in mice, suggesting that VacA inhibition may be involved. However, further studies are needed to determine the specific effect(s) (e.g., loss of attachment mechanisms, virulence factors, host membrane integrity, etc.)…”
mentioning
confidence: 99%